A mathematical problem-solving framework-based Integrated STEM: Theory and practice - Ijtihadi Kamilia Amalina; Tibor Vidákovich (SAINTIS Publishing, 2022)
STEM problem-solving is a core standard in education to tackle the 21st-century challenge. However, the under-represented mathematics in STEM assessment has become an issue. Moreover, the existing frameworks of STEM problem-solving are suitable for assessing activity during teaching and learning. This study covers the limitations by developing a new mathematical problem-solving-based integrated STEM framework and applying it into practice. The new framework combines and integrates frameworks in every STEM discipline. It applies in developing scenario based-test with prompting questions to show the practical use of the framework. The test was administered to 31 of 7th graders students (M=12.29, SD=.46) to prove the consistency of the new framework and the effective role of scenario and prompting questions. The results revealed four types of flows in the problem-solving process posed by students with different in evaluating, representing, and designing phases. The flow of problem-solving and the indicators in a new model were consistent but shown as a dependent process. The scenario and prompting questions worked effectively regardless of a multidimensional prompting question. Several recommendations for developing a test based on the new framework are discussed. Quantitative analysis with large sample size is required for future study.